(untitled) - Isakov, Victor (Indianapolis, IN, 2006)
This comprehensive book guides readers through Microsoft's brand- new SQL 2005 certification: Microsoft Certified IT Professional Developer for SQL Server 2005 (Exam 70441). Topics covered include writing SQL queries, designing and implementing programming objects, database optimization, designing databases at both the conceptual and logical levels, and implementing databases at the physical level.Aimed at candidates for this exam, namely professional database developers who are responsible for designing and implementing database solutions using SQL Server 2005. The CD-ROM features leading-edge exam prep software with test engine plus hundreds of practice questions and electronic flashcards
Keywords: Electronic data processing personnel,Microsoft software,Database design,Người xử lý dữ liệu điện tử,Phần mềm Microsoft,Thiết kế cơ sở dữ liệu; Certification,Examinations,Examinations,Chứng nhận,Chứng nhận,Chứng nhận